Reproductive Health Problems of Women with Visual Impairment and Solutions - Aylin Taner; Özlem Demirel Bozkurt (Dokuz Eylul University, 2021)
Women with visual disability experience problems related to reproductive health, such as menstrual cycle, sexual health, pregnancy, delivery method, breastfeeding and having a child, family planning, visiting for gynecological examination and annual routine check-up, as well as problems related to accessing healthcare services, receiving education and care. When providing education and counseling regarding these problems and their solutions, it is required to utilize tactual and audial materials in order to provide optimal benefit. The act of seeing is responsible for obtaining information and any change in this organ will reduce the individual's capacity. If nurses know the reasons of visual disability and its impact on the individual's learning, this will provide benefit to the formation of educational plans to be arranged for reproductive health. Fact that the brochures and leaflets prepared to inform women about reproductive health are written or vocalized in the Braille Alphabet, enables women with visual disability to reach the information. Nurses should be trained in approaching and providing education and counseling to individuals with visual disability. The aim of this review is to draw attention to the definitions and reasons for a visual disability that affects the way of receiving education/counseling and to raise awareness in nurses related to the problems experienced by women regarding reproductive health and the solutions of these problems.